Application of geomarketing to coastal tourism areas - Peñarubia-Zaragoza,María Pilar (2019)
Geomarketing allows geographic units to be defined with a certain degree of homogeneity in terms of tourist preferences, behaviours, needs, expectations, buying and consumption patterns, and analogous attitudes. The result is a territorial segmentation of the demand in accordance with the geographic characteristics of tourism areas. The objective of this work is to analyse the strengths and weaknesses of applying geomarketing to the territorial segmentation of demand in coastal tourism areas. An empirical analysis of hotels specialising in family tourism in tourist accommodation establishments in Costa Adeje (Spain) is presented. The main conclusion is that the tourist accommodation variable is essential for any segmentation process and even for the micro-segmentation of coastal tourism areas. It allows similar consumers to be grouped in a market from a demand perspective based on shared needs, habits or attitudes and also from the supply side, according to territorial characteristics. Therefore, the territorial aspect is essential for public and private decision-making processes. This makes geomarketing an ideal technique for understanding tourists.